THE EXPERIENCE OF SWITCHING TO THE SECOND TNF INHIBITOR IN A PATIENT WITH SEVERE JUVENILE POLYARTHRITIS AND RESISTANCE TO THE FIRST TNF-BLOCKER - Ekaterina I. Alexeeva; Tatiana M. Dvoryakovskaya; Rina V. Denisova; Olga L. Lomakina; Anna V. Karaseva (Вопросы современной педиатрии)
The article presents  a case  of a severe  progressive  course  of polyarticular  juvenile idiopathic arthritis,  debuting  at an early age, refractory to the therapy with methotrexate, cyclosporine, and glucocorticosteroids.  A clinical example demonstrates that switching to the second TNF  inhibitor in the case of developing secondary resistance to the first drug from this group provides restoration of the therapeutic effect and is not accompanied by serious adverse events. Six months after switching to adalimumab, due to the «escape» of the effect of etanercept, the inflammatory changes in the patient were reversed; the volume of movements in the joints increased, and the laboratory parameters of the disease activity were normalized. After 1 year, there was a remission of the disease. The child managed to completely eliminate glucocorticosteroids for oral ingestion. The duration of the joint syndrome remission was 3 years. Adverse events were not serious and did not become a basis for drug withdrawal.